Clinical course of type 1 autoimmune pancreatitis patients without steroid treatment: a Japanese multicenter study of 97 patients. (23rd March 2018) - Kubota, Kensuke; Kamisawa, Terumi; Hirano, Kenji; Hirooka, Yoshiki; Uchida, Kazushige; Ikeura, Tsukasa; Shiomi, Hideyuki; Ohara, Hirotaka; Shimizu, Kyoko; Arakura, Norikazu; Kanno, Atsushi; Sakagami, Junichi; et al.
Abstract: Background: Sporadic autoimmune pancreatitis (AIP) cases showing remission without steroid treatment have been reported, however, the clinical course of these patients has not been clarified. This study sought to clarify the clinical course in AIP patients with hesitation for steroid treatment. Methods: We collected clinical data for AIP patients from high‐volume centers in Japan. Data for AIP patients with and those without steroid treatment (steroid treatment vs. wait and see policy or W&S) were then compared. The primary point was the relapse‐free survival rate (RFS) in patients with and those without steroid treatment, as determined using Kaplan–Meier curve. The secondary point was the identification of predictors of remission and risks of relapse in AIP patients without steroid treatment. Results: There were 510 AIP patients in the steroid treatment group and 97 patients in the W&S group. Overall, 55.7% (54/97) of type 1 AIP patients in the W&S group experienced transient remission without steroid treatment. The W&S group had a significantly higher patient age and significantly lower incidences of jaundice, diffuse pancreas swelling, proximal‐type sclerosing cholangitis, and stent placement and a lower remission rate than the steroid treatment group (each P  <   0.05). The RFS reached a plateau at 10 years in both the W&S group (50%) and steroid treatment group (52.9%). As for the RFS (W&S vs. group with steroid), 89.4% vs. 74.4% within 3 years, 81.8% vs. 65.3% within 5 years, and 50% vs. 52.9% within 10 years (log‐rank, P  =   0.064). Female gender (OR 0.340, P  =   0.027) and stent placement for jaundice (OR 4.552, P  =   0.008) were identified as predictors of transient remission in the W&S group. New‐onset diabetes mellitus (OR 8.333, P  =   0.012) and the presence of extensive multi‐organ involvement (OR 35, P  =   0.006) were identified as risks of relapse in the W&S group. Conclusion: Some type 1 AIP patients without steroid treatment experience transient remission. These cases tend to have lower disease activities than AIP patients receiving steroids. Female gender and stent placement for jaundice may be predictors of transient remission among patients not receiving steroid treatment, however, relapses can occur in these patients with new‐onset diabetes mellitus and the presence of extensive multi‐organ involvement. Therefore, steroid treatment is still imperative for these patients. Abstract : Highlight Some autoimmune pancreatitis patients exhibit transient remission without steroid treatment. In this retrospective multicenter study with long‐term follow‐up, Kubota and colleagues revealed that female gender and stent placement for jaundice may be predictors of remission in such patients. Patients with new‐onset diabetes mellitus and extensive multi‐organ involvement are prone to relapse.